Strategies of organizational development of entrepreneurial activity in global environment - Parkhomenko, Nataliia (Management and Entrepreneurship: Trends of Development, 2025)
The relevance of the topic is due to the fact that in conditions of high uncertainty, increased global competition and rapid transformation, there is a need to form strategies that will ensure long-term sustainability.The purpose of the research is to theoretically substantiate and practically analyze strategies for organizational development of business activities in the global environment.The research was carried out on the basis of a comprehensive methodological approach, which involves a combination of theoretical analysis and empirical research. At the theoretical stage of the study, a systematic analysis of scientific literature was conducted that highlight the issues of strategic management of organizational development of business activities. The empirical stage of the study involved the use of questionnaires among business entities, which made it possible to identify practical features of the implementation of organizational development strategies for business activities and assess their effectiveness. SWOT analysis allowed assessing the strengths and weaknesses of the strategic organizational development of business entities. At the final stage, the results of theoretical and empirical analysis were generalized and integrated, which made it possible to formulate practical recommendations for their implementation and assess the impact of strategies on the competitiveness and sustainability of enterprises.As a result of the research, the role of organizational development of entrepreneurial activity in strategic management was clarified, innovative approaches to the formation of organizational development strategies of entrepreneurial activity and the classification of organizational development strategies were systematized, and practical recommendations for the implementation of organizational development strategies of entrepreneurial activity were provided. The scientific novelty of the reseach lies in the complex combination of theoretical justification and practical assessment of organizational development strategies of entrepreneurial activity.JEL Classification: L29, M21, O20